2011
DOI: 10.5433/1679-0359.2011v32n1p327
|View full text |Cite
|
Sign up to set email alerts
|

Artéria renal dupla em gato

Abstract: ResumoO conhecimento das variações nos vasos renais possui importância em um programa de sistematização da anatomia radiológica e cirúrgica, tanto para o homem quanto para animais destinados a pesquisa, ensino e treinamento cirúrgico. As artérias renais têm sido estudas tanto radiograficamente quanto através de dissecção. Atenção particular é dada ao estudo desses vasos enfatizando as variações entre as diferentes espécies animais. O local de origem das artérias renais a partir da aorta abdominal varia de acor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
3
0
3
Order By: Relevance
“…The renal arteries (right and left) of the brown brocket deer were bifurcated in two main sector arteries, cranial and caudal; this renal artery pattern was described to the crabeating raccoon (Barcelos et al, 2012) and ovines (Carvalho 2007). The organ did not present accessory renal arteries or double renal arteries, supporting the anatomical findings from Research, Society andDevelopment, v. 9, n. 10, e4929108868, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8868 caprines (Abidu-Figueiredo et al, 2009), dogs (Alonso & Abidu-Figueiredo 2008) and cats (Pestana et al, 2011).…”
Section: Resultssupporting
confidence: 67%
“…The renal arteries (right and left) of the brown brocket deer were bifurcated in two main sector arteries, cranial and caudal; this renal artery pattern was described to the crabeating raccoon (Barcelos et al, 2012) and ovines (Carvalho 2007). The organ did not present accessory renal arteries or double renal arteries, supporting the anatomical findings from Research, Society andDevelopment, v. 9, n. 10, e4929108868, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8868 caprines (Abidu-Figueiredo et al, 2009), dogs (Alonso & Abidu-Figueiredo 2008) and cats (Pestana et al, 2011).…”
Section: Resultssupporting
confidence: 67%
“…We noted the presence of the BR bilaterally and unilaterally respectively in 18 (53%) and 5 (14.7%) of the 34 dogs dissected compared with 40 (40%) bilateral and 15 (15%) unilateral of the 100 dogs dissected by Pestana et al [ 61 ], 110 (33.74%) bilateral and 65 (19.94%) unilateral of the 326 dogs dissected by Santos Junior et al [ 62 ], and 35 (38.9%) of the 90 dogs dissected by Wakuri and Kano [ 63 ]. The insertion of the BR muscle was variably attached through a long and distinct tendon (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Numerical variations of the renal arteries have been described in dogs (OLIVEIRA and GUIMARÃES, 2007;ALONSO and ABIDU-FIGUEIREDO, 2008), cats (PESTANA et al, 2011), andrabbits (ALMEIDA et al, 2013). These reported variations are more frequently observed in arteries than in veins, although CAMPOS et al (2014) and STOCCO et al (2014) reported double renal veins in both kidneys, and triplet veins in only the right kidney, in cats, respectively.…”
Section: Discussionmentioning
confidence: 99%